A method for detecting the content of preservatives in food

Through a multi-step detection method, including mixing samples with pure water, processing of modified adsorbents and chemical reagents, ultrasonic and centrifugal filtration, n-hexane extraction and liquid chromatography, the problem of preservative detection in food is solved, rapid, accurate and low-cost detection effect is achieved, and food safety is improved.

CN119086749BActive Publication Date: 2025-04-11长治市综合检验检测中心
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411220672.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-04-11
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect the content of preservatives in food, resulting in frequent occurrence of preservatives exceeding the standard in food, affecting food safety.

Method used

A detection method including multi-step treatment is adopted: firstly mix the food sample with pure water, add modified adsorbent, potassium ferrocyanide solution and zinc acetate solution, and perform water bath sonication and centrifugal filtration, followed by n-hexane extraction and liquid chromatography to accurately detect the content of the preservative.

Benefits of technology

It realizes fast, accurate, simple and low-cost food preservative detection, and can be widely used in foods of different states, improving testing efficiency and food safety, and reducing testing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119086749B_ABST
    Figure CN119086749B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for detecting the content of preservatives in food, which relates to the field of detection technology and comprises the following steps: (1) first, classifying the samples to be tested according to their states: solid samples, liquid samples, and gel samples; (2) obtaining a first mixed solution; fixing the volume of the first mixed solution; (3) obtaining a first aqueous phase; (4) obtaining a second aqueous phase; (5) filtering the second aqueous phase through a filter membrane for liquid chromatography determination; injecting a mixed standard series of working solutions into a liquid chromatograph respectively, determining the corresponding peak areas, and drawing a standard curve with the mass concentration of the mixed standard series of working solutions as the horizontal coordinate and the peak area as the vertical coordinate; the method of the present invention has the characteristics of rapid, accurate, simple and low-cost detection, and can be widely used in the detection of preservatives in several types of food including solid, liquid, semi-solid, etc., can greatly improve the detection efficiency of preservatives in food, and can effectively control the detection cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of detection technology, in particular to a method for detecting the content of preservatives in food. Background Art

[0002] Food additives are artificial or natural substances added to food to improve its quality, color, aroma, and taste, as well as for preservation, freshness, and processing needs. They have been widely used in industrially processed foods.

[0003] Food preservatives have a sustained inhibitory effect on the growth of microorganisms whose metabolic substrates are spoilage. What is important is that they can inhibit the occurrence of the most susceptible spoilage under different circumstances, especially when general sterilization is inadequate and still have a sustained effect.

[0004] With the rapid development of industrial processed food, incidents of excessive food additives have emerged one after another. Studies have shown that excessive intake of preservatives such as benzoic acid and sorbic acid can cause asthma, urticaria and convulsions in sensitive individuals, and in severe cases can even cause damage to the nervous system.

[0005] However, due to production cost constraints and unawareness of the hazards of excessive preservatives, many food manufacturers violate regulations and illegally use, abuse, and use excessive doses of food preservatives, resulting in excessive amounts of preservative additives in many foods. The intake of excessive preservatives will have certain negative effects on physical health.

[0006] Based on this, a method for detecting the content of preservatives in food is provided to solve the existing technical problems. Summary of the invention

[0007] The purpose of the present invention is to provide a method for detecting the content of preservatives in food to solve the deficiencies in the prior art.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A method for detecting the content of preservatives in food comprises the following steps:

[0010] (1) First, the samples to be tested are classified according to their state: solid samples, liquid samples, and gel samples;

[0011] (2) crushing the solid sample to obtain solid powder, then adding the solid powder sample to pure water, stirring and mixing, and obtaining a first mixed solution;

[0012] For a liquid sample, directly add it into pure water, stir and mix, and obtain a first mixed solution;

[0013] The gel sample is added into pure water, heated to 80°C, kept warm, and stirred at 5000r / min for 10min to obtain a first mixed solution;

[0014] (3) adding the modified adsorbent to the first mixed solution obtained above, stirring for 10 min, then adding potassium ferrocyanide solution and zinc acetate solution, ultrasonically treating in a water bath at 50° C. for 20-30 min, then centrifuging at 8000 r / min, filtering, transferring the aqueous phase, and obtaining a first aqueous phase;

[0015] The mixing ratio of the first mixed liquid and the modified adsorbent is 50mL:3-5g;

[0016] The volume ratio of the first mixed solution, potassium ferrocyanide solution, and zinc acetate solution is 25:1:1;

[0017] The concentration of the potassium ferrocyanide solution is 92 g / L;

[0018] The concentration of the zinc acetate solution is 183 g / L;

[0019] (4) adding n-hexane to the first aqueous phase for extraction, then subjecting it to ultrasonic treatment for 5-10 min, and then subjecting it to centrifugation at a speed of 8000 r / min, standing for 2 hours, removing the organic phase, and obtaining a second aqueous phase;

[0020] Wherein, the volume ratio of the first water phase to n-hexane is 5:1;

[0021] (5) Take 20 mL of the second aqueous phase and filter it through a 0.22 μm filter membrane for liquid chromatography determination;

[0022] Inject the mixed standard series working solutions into the liquid chromatograph respectively, measure the corresponding peak areas, and draw a standard curve with the mass concentration of the mixed standard series working solutions as the abscissa and the peak area as the ordinate;

[0023] The filtered second aqueous phase is injected into a liquid chromatograph to obtain the peak area, and the mass concentration of the preservative in the test solution is obtained according to the standard curve;

[0024] The preservatives include benzoic acid, sorbic acid and saccharin sodium.

[0025] As a further technical solution: in step (2), the mixing ratio of solid powder and pure water is 2 g: 25 mL;

[0026] The mixing ratio of liquid sample and pure water is 2g:25mL;

[0027] The mixing ratio of the gel sample and pure water is 2g:25mL.

[0028] As a further technical solution: the preparation method of the modified adsorbent in step (3) is:

[0029] The pretreated cellulose nanocrystals were added to the sodium hydroxide solution, the temperature was adjusted to 10°C, the mixture was stirred for 15 minutes, and then urea was added, the mixture was stirred and mixed evenly, the temperature was adjusted to 18°C, and the mixture was stirred for 30 minutes to obtain a mixed solution;

[0030] The mixing ratio of pretreated cellulose nanocrystals and sodium hydroxide solution is 10-12 g: 300 mL;

[0031] The molar ratio of urea to sodium hydroxide is 7:5;

[0032] Adding sodium alginate to deionized water, stirring and mixing evenly to obtain a sodium alginate solution;

[0033] The mass fraction of sodium alginate solution is 5%;

[0034] The sodium alginate solution was added dropwise to the mixed solution and stirred for 10 min to obtain a treated solution;

[0035] The volume ratio of sodium alginate solution and mixed solution is 1:10-12;

[0036] The montmorillonite is placed in a resistance furnace for calcination for 30 minutes, and then cooled to room temperature to obtain calcined montmorillonite;

[0037] Calcination temperature 450-460℃;

[0038] The calcined montmorillonite was added to the treatment liquid, the temperature was adjusted to 50°C, the mixture was stirred for 40 minutes, the calcium chloride solution was added dropwise, the mixture was stirred for 2 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain a modified adsorbent.

[0039] As a further technical solution, the method for preparing pretreated cellulose nanocrystals is:

[0040] First, KH550 was added to the ethanol solution, the temperature was adjusted to 60°C, kept warm, and stirred for 30 minutes to obtain a KH550 solution;

[0041] Cellulose nanocrystals were added to the KH550 solution, the temperature was adjusted to 75°C, the pH was adjusted to 3.5, the solution was stirred for 4 hours, and then filtered, washed to neutrality, and dried at 70°C for 1 hour to obtain pretreated cellulose nanocrystals.

[0042] As a further technical solution, the mass ratio of the KH550 and ethanol solution is 1:5;

[0043] Among them, the mass fraction of ethanol solution is 95%;

[0044] The mixing ratio of the cellulose nanocrystals and the KH550 solution is 22-25 g: 250 mL.

[0045] As a further technical solution, the mixing ratio of the calcined montmorillonite and the treatment liquid is 30-33 g: 280 mL;

[0046] The mass fraction of calcium chloride solution is 10%;

[0047] The volume ratio of calcium chloride solution to treatment solution is 1:5.

[0048] As a further technical solution, the liquid chromatograph parameters are:

[0049] Chromatographic column: C18 column, column length 250 mm, inner diameter 4.6 mm, particle size 5 μm;

[0050] Mobile phase: 5% methanol + 95% ammonium acetate solution;

[0051] Flow rate: 1 mL / min;

[0052] Detection wavelength: 230nm;

[0053] Injection volume: 10 μL.

[0054] As a further technical solution, the preservative content calculation formula is:

[0055] X = ρV / 1000m;

[0056] X—preservative content in the sample to be tested, in grams per kilogram (g / kg);

[0057] ρ—mass concentration of the sample to be tested in the first mixed solution obtained from the standard curve, in milligrams per liter (mg / L);

[0058] V—volume of the first mixed solution, in milliliters (mL);

[0059] m—mass of the sample to be tested, in grams (g);

[0060] 1000—conversion factor from mg / kg to g / kg; the calculation result of the preservative content is rounded to 3 significant figures.

[0061] As a further technical solution, the ultrasonic treatment is performed for 5-10 minutes, including:

[0062] Volume of n-hexane added for extraction;

[0063] extracting the liquid volume of the first aqueous phase;

[0064] The initial frequency and target frequency of ultrasound are obtained using the added volume of n-hexane and the liquid volume of the first aqueous phase, wherein the initial frequency of ultrasound is obtained by the following formula:

[0065]

[0066] Among them, F c Indicates the initial frequency of ultrasound; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0067] At the same time, the target frequency is obtained by the following formula:

[0068]

[0069] Among them, F m Indicates the target frequency; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0070] The first aqueous phase to which n-hexane is added is ultrasonically treated according to the initial frequency, and the ultrasonic frequency of the ultrasonic treatment is gradually adjusted from the initial frequency to the target frequency, and at the same time, the continuous duration of the ultrasonic treatment at the target frequency is ensured to be not less than 0.4t m , where t m It indicates the total duration of the preset ultrasonic treatment, and the total duration of the ultrasonic treatment ranges from 5 to 10 minutes.

[0071] Beneficial effects:

[0072] The method of the present invention has the characteristics of rapid, accurate, simple and low-cost detection, and can be widely used in the detection of preservatives in several types of food including solid, liquid, semi-solid, etc. It can greatly improve the detection efficiency of preservatives in food, and can effectively control the detection cost and shorten the detection cycle.

[0073] By adopting the detection method of the present invention, food safety can be effectively improved, and high social benefits can be achieved.

[0074] The detection method of the present invention can accurately and efficiently detect the preservative content. In the process of preservative detection, the modified adsorbent is used for treatment, which greatly improves the accuracy of the detection result.

[0075] The interfering impurities are separated mainly through physical or chemical action through modified adsorbent treatment to reduce the interference of impurities on the test results.

[0076] Through the selective adsorption of modified adsorbents, after adsorption separation, the concentration of the target preservative can be significantly increased, thereby enhancing the strength of the detection signal and improving the sensitivity and accuracy of the detection. Since the test samples often contain multiple components, these components may interfere with the test results. Through the treatment of modified adsorbents, these interfering substances can be greatly removed or reduced, the matrix effect can be reduced, and the detection efficiency and accuracy can be improved.

[0077] The present invention adopts a specially made modified adsorbent, which can significantly optimize the detection conditions, making the detection process smoother, thereby ensuring that the detection results are more stable and repeatable.

[0078] The treatment of the modified adsorbent prepared by the present invention can remove interfering components, which can greatly shorten the detection time and improve the detection efficiency, so that the detection method of the present invention can be applied to the rapid screening of large quantities of samples, thereby broadening the application field. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 This is the liquid chromatogram of 1 mg / L benzoic acid, sorbic acid and saccharin sodium standard solution. DETAILED DESCRIPTION

[0080] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] Example 1

[0082] A method for detecting the content of preservatives in food comprises the following steps:

[0083] (1) First, the samples to be tested are classified according to their state: solid samples, liquid samples, and gel samples;

[0084] (2) crushing the solid sample to obtain solid powder, then adding the solid powder sample to pure water, stirring and mixing, and obtaining a first mixed solution;

[0085] For a liquid sample, directly add it into pure water, stir and mix, and obtain a first mixed solution;

[0086] For the gel sample, add it to pure water, heat it to 80°C, keep it warm, and stir it at 5000r / min for 10 minutes to obtain the first mixed solution; the mixing ratio of solid powder to pure water is 2g:25mL;

[0087] The mixing ratio of liquid sample and pure water is 2g:25mL;

[0088] The mixing ratio of the gel sample and pure water is 2g:25mL.

[0089] (3) adding the modified adsorbent to the first mixed solution obtained above, stirring for 10 min, then adding potassium ferrocyanide solution and zinc acetate solution, ultrasonically treating in a water bath at 50° C. for 20 min, then centrifuging at 8000 r / min, filtering, transferring the aqueous phase, and obtaining a first aqueous phase;

[0090] The mixing ratio of the first mixed liquid and the modified adsorbent is 50mL:3g;

[0091] The volume ratio of the first mixed solution, potassium ferrocyanide solution, and zinc acetate solution is 25:1:1;

[0092] The concentration of the potassium ferrocyanide solution is 92 g / L;

[0093] The concentration of the zinc acetate solution is 183 g / L; the preparation method of the modified adsorbent is:

[0094] The pretreated cellulose nanocrystals were added to the sodium hydroxide solution, the temperature was adjusted to 10°C, the mixture was stirred for 15 minutes, and then urea was added, the mixture was stirred and mixed evenly, the temperature was adjusted to 18°C, and the mixture was stirred for 30 minutes to obtain a mixed solution;

[0095] The mixing ratio of pretreated cellulose nanocrystals and sodium hydroxide solution was 10 g: 300 mL;

[0096] The molar ratio of urea to sodium hydroxide is 7:5;

[0097] Adding sodium alginate to deionized water, stirring and mixing evenly to obtain a sodium alginate solution;

[0098] The mass fraction of sodium alginate solution is 5%;

[0099] The sodium alginate solution was added dropwise to the mixed solution and stirred for 10 min to obtain a treated solution;

[0100] The volume ratio of sodium alginate solution and mixed solution is 1:10;

[0101] The montmorillonite is placed in a resistance furnace for calcination for 30 minutes, and then cooled to room temperature to obtain calcined montmorillonite;

[0102] Calcination temperature: 450℃;

[0103] Calcined montmorillonite was added to the treatment solution, the temperature was adjusted to 50°C, the mixture was stirred for 40 minutes, calcium chloride solution was added dropwise, stirring was continued for 2 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain a modified adsorbent; the preparation method of pretreated cellulose nanocrystals is as follows:

[0104] First, KH550 was added to the ethanol solution, the temperature was adjusted to 60°C, kept warm, and stirred for 30 minutes to obtain a KH550 solution;

[0105] The cellulose nanocrystals were added to the KH550 solution, the temperature was adjusted to 75°C, the pH was adjusted to 3.5, the mixture was stirred for 4 hours, and then filtered, washed to neutrality, and dried at 70°C for 1 hour to obtain pretreated cellulose nanocrystals; the mass ratio of KH550 to ethanol solution was 1:5;

[0106] Among them, the mass fraction of ethanol solution is 95%;

[0107] The mixing ratio of the cellulose nanocrystals and the KH550 solution is 22 g: 250 mL; the mixing ratio of the calcined montmorillonite and the treatment solution is 30 g: 280 mL;

[0108] The mass fraction of calcium chloride solution is 10%;

[0109] The volume ratio of calcium chloride solution to treatment solution is 1:5.

[0110] (4) adding n-hexane to the first aqueous phase for extraction, then subjecting it to ultrasonic treatment for 5 min, and then subjecting it to centrifugation at a speed of 8000 r / min, standing for 2 hours, removing the organic phase, and obtaining a second aqueous phase;

[0111] Wherein, the volume ratio of the first water phase to n-hexane is 5:1;

[0112] (5) Take 20 mL of the second aqueous phase and filter it through a 0.22 μm filter membrane for liquid chromatography determination;

[0113] Inject the mixed standard series working solutions into the liquid chromatograph respectively, measure the corresponding peak areas, and draw a standard curve with the mass concentration of the mixed standard series working solutions as the abscissa and the peak area as the ordinate;

[0114] The filtered second aqueous phase is injected into a liquid chromatograph to obtain the peak area, and the mass concentration of the preservative in the test solution is obtained according to the standard curve;

[0115] The preservatives include benzoic acid, sorbic acid and saccharin sodium.

[0116] The liquid chromatography parameters are:

[0117] Chromatographic column: C18 column, column length 250 mm, inner diameter 4.6 mm, particle size 5 μm;

[0118] Mobile phase: 5% methanol + 95% ammonium acetate solution;

[0119] Flow rate: 1 mL / min;

[0120] Detection wavelength: 230nm;

[0121] Injection volume: 10 μL.

[0122] The preservative content calculation formula is:

[0123] X = ρV / 1000m;

[0124] X—preservative content in the sample to be tested, in grams per kilogram (g / kg);

[0125] ρ—mass concentration of the sample to be tested in the first mixed solution obtained from the standard curve, in milligrams per liter (mg / L);

[0126] V—volume of the first mixed solution, in milliliters (mL);

[0127] m—mass of the sample to be tested, in grams (g);

[0128] 1000—Conversion factor from mg / kg to g / kg.

[0129] The calculated result of preservative content shall be rounded to 3 significant figures.

[0130] Specifically, after 5-10 minutes of ultrasound, the following steps are performed:

[0131] Volume of n-hexane added for extraction;

[0132] extracting the liquid volume of the first aqueous phase;

[0133] The initial frequency and target frequency of ultrasound are obtained using the added volume of n-hexane and the liquid volume of the first aqueous phase, wherein the initial frequency of ultrasound is obtained by the following formula:

[0134]

[0135] Among them, F cIndicates the initial frequency of ultrasound; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0136] At the same time, the target frequency is obtained by the following formula:

[0137]

[0138] Among them, F m Indicates the target frequency; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0139] The first aqueous phase to which n-hexane is added is ultrasonically treated according to the initial frequency, and the ultrasonic frequency of the ultrasonic treatment is gradually adjusted from the initial frequency to the target frequency, and at the same time, the continuous duration of the ultrasonic treatment at the target frequency is ensured to be not less than 0.4t m , where t m It indicates the total duration of the preset ultrasonic treatment, and the total duration of the ultrasonic treatment ranges from 5 to 10 minutes.

[0140] The technical effect of the above technical scheme is: by introducing the added volume of n-hexane (Vz) and the liquid volume of the first aqueous phase (Vy) as variables, combined with the preset ultrasonic initial reference frequency (F0), the frequency fluctuation amplitude (Ff) of the ultrasonic vibration device during operation, the concentration percentage value (c) of n-hexane, and the maximum ultrasonic frequency (Fd) corresponding to the first aqueous phase to which n-hexane is added, the initial frequency (Fc) and the target frequency (Fm) of the ultrasonic treatment are accurately calculated. This frequency calculation method based on specific experimental conditions can ensure that the ultrasonic treatment process is more accurate and effective. The ultrasonic treatment method of gradually adjusting from the initial frequency to the target frequency helps to gradually optimize the treatment effect during the ultrasonic treatment process. The initial frequency may be low to avoid excessive impact or damage to the sample, while the target frequency is set according to the experimental conditions to achieve the best ultrasonic treatment effect. This frequency adjustment strategy helps to reduce potential damage to the sample while ensuring the treatment effect. The technical scheme clearly stipulates that the total duration (tm) of the ultrasonic treatment has a value range of 5-10min, and requires that the continuous duration of the target frequency for ultrasonic treatment is not less than 0.4tm. This regulation ensures that the ultrasonic treatment has enough time to fully act on the sample, so as to achieve the expected treatment effect. At the same time, it also avoids unnecessary energy consumption and sample damage that may be caused by too long treatment time. By accurately calculating the initial frequency and target frequency of the ultrasonic treatment, and strictly controlling the duration of the ultrasonic treatment and the frequency adjustment strategy, this technical solution helps to improve the repeatability and stability of the experiment. This is of great significance to scientific research, industrial production and other fields, and can ensure the reliability and consistency of experimental results.

[0141] In summary, this technical solution achieves effective ultrasonic treatment of the first aqueous phase added with n-hexane by accurately controlling the ultrasonic treatment process, optimizing the ultrasonic treatment effect, ensuring the ultrasonic treatment time, and improving the repeatability and stability of the experiment.

[0142] Example 2

[0143] A method for detecting the content of preservatives in food comprises the following steps:

[0144] (1) First, the samples to be tested are classified according to their state: solid samples, liquid samples, and gel samples;

[0145] (2) crushing the solid sample to obtain solid powder, then adding the solid powder sample to pure water, stirring and mixing, and obtaining a first mixed solution;

[0146] For a liquid sample, directly add it into pure water, stir and mix, and obtain a first mixed solution;

[0147] For the gel sample, add it to pure water, heat it to 80°C, keep it warm, and stir it at 5000r / min for 10 minutes to obtain the first mixed solution; the mixing ratio of solid powder to pure water is 2g:25mL;

[0148] The mixing ratio of liquid sample and pure water is 2g:25mL;

[0149] The mixing ratio of the gel sample and pure water is 2g:25mL.

[0150] (3) adding the modified adsorbent to the first mixed solution obtained above, stirring for 10 min, then adding potassium ferrocyanide solution and zinc acetate solution, ultrasonically treating in a water bath at 50° C. for 25 min, then centrifuging at 8000 r / min, filtering, transferring the aqueous phase, and obtaining a first aqueous phase;

[0151] The mixing ratio of the first mixed liquid and the modified adsorbent is 50 mL: 3.5 g;

[0152] The volume ratio of the first mixed solution, potassium ferrocyanide solution, and zinc acetate solution is 25:1:1;

[0153] The concentration of the potassium ferrocyanide solution is 92 g / L;

[0154] The concentration of the zinc acetate solution is 183 g / L; the preparation method of the modified adsorbent is:

[0155] The pretreated cellulose nanocrystals were added to the sodium hydroxide solution, the temperature was adjusted to 10°C, the mixture was stirred for 15 minutes, and then urea was added, the mixture was stirred and mixed evenly, the temperature was adjusted to 18°C, and the mixture was stirred for 30 minutes to obtain a mixed solution;

[0156] The mixing ratio of pretreated cellulose nanocrystals and sodium hydroxide solution was 11 g: 300 mL;

[0157] The molar ratio of urea to sodium hydroxide is 7:5;

[0158] Adding sodium alginate to deionized water, stirring and mixing evenly to obtain a sodium alginate solution;

[0159] The mass fraction of sodium alginate solution is 5%;

[0160] The sodium alginate solution was added dropwise to the mixed solution and stirred for 10 min to obtain a treated solution;

[0161] The volume ratio of sodium alginate solution and mixed solution is 1:10.5;

[0162] The montmorillonite is placed in a resistance furnace for calcination for 30 minutes, and then cooled to room temperature to obtain calcined montmorillonite;

[0163] Calcination temperature 452℃;

[0164] Calcined montmorillonite was added to the treatment solution, the temperature was adjusted to 50°C, the mixture was stirred for 40 minutes, calcium chloride solution was added dropwise, stirring was continued for 2 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain a modified adsorbent; the preparation method of pretreated cellulose nanocrystals is as follows:

[0165] First, KH550 was added to the ethanol solution, the temperature was adjusted to 60°C, kept warm, and stirred for 30 minutes to obtain a KH550 solution;

[0166] The cellulose nanocrystals were added to the KH550 solution, the temperature was adjusted to 75°C, the pH was adjusted to 3.5, the mixture was stirred for 4 hours, and then filtered, washed to neutrality, and dried at 70°C for 1 hour to obtain pretreated cellulose nanocrystals; the mass ratio of KH550 to ethanol solution was 1:5;

[0167] Among them, the mass fraction of ethanol solution is 95%;

[0168] The mixing ratio of the cellulose nanocrystals and the KH550 solution is 23 g: 250 mL; the mixing ratio of the calcined montmorillonite and the treatment solution is 31 g: 280 mL;

[0169] The mass fraction of calcium chloride solution is 10%;

[0170] The volume ratio of calcium chloride solution to treatment solution is 1:5.

[0171] (4) adding n-hexane to the first aqueous phase for extraction, then subjecting it to ultrasonic treatment for 8 min, and then subjecting it to centrifugation at a speed of 8000 r / min, standing for 2 hours, removing the organic phase, and obtaining a second aqueous phase;

[0172] Wherein, the volume ratio of the first water phase to n-hexane is 5:1;

[0173] (5) Take 20 mL of the second aqueous phase and filter it through a 0.22 μm filter membrane for liquid chromatography determination;

[0174] Inject the mixed standard series working solutions into the liquid chromatograph respectively, measure the corresponding peak areas, and draw a standard curve with the mass concentration of the mixed standard series working solutions as the abscissa and the peak area as the ordinate;

[0175] The filtered second aqueous phase is injected into a liquid chromatograph to obtain the peak area, and the mass concentration of the preservative in the test solution is obtained according to the standard curve;

[0176] The preservatives include benzoic acid, sorbic acid and saccharin sodium.

[0177] The liquid chromatography parameters are:

[0178] Chromatographic column: C18 column, column length 250 mm, inner diameter 4.6 mm, particle size 5 μm;

[0179] Mobile phase: 5% methanol + 95% ammonium acetate solution;

[0180] Flow rate: 1 mL / min;

[0181] Detection wavelength: 230nm;

[0182] Injection volume: 10 μL.

[0183] The preservative content calculation formula is:

[0184] X = ρV / 1000m;

[0185] X—preservative content in the sample to be tested, in grams per kilogram (g / kg);

[0186] ρ—mass concentration of the sample to be tested in the first mixed solution obtained from the standard curve, in milligrams per liter (mg / L);

[0187] V—volume of the first mixed solution, in milliliters (mL);

[0188] m—mass of the sample to be tested, in grams (g);

[0189] 1000—Conversion factor from mg / kg to g / kg.

[0190] The calculated result of preservative content shall be rounded to 3 significant figures.

[0191] Specifically, after 5-10 minutes of ultrasound, the following steps are performed:

[0192] Volume of n-hexane added for extraction;

[0193] extracting the liquid volume of the first aqueous phase;

[0194] The initial frequency and target frequency of ultrasound are obtained using the added volume of n-hexane and the liquid volume of the first aqueous phase, wherein the initial frequency of ultrasound is obtained by the following formula:

[0195]

[0196] Among them, F c Indicates the initial frequency of ultrasound; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F fIndicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0197] At the same time, the target frequency is obtained by the following formula:

[0198]

[0199] Among them, F m Indicates the target frequency; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0200] The first aqueous phase to which n-hexane is added is ultrasonically treated according to the initial frequency, and the ultrasonic frequency of the ultrasonic treatment is gradually adjusted from the initial frequency to the target frequency, and at the same time, the continuous duration of the ultrasonic treatment at the target frequency is ensured to be not less than 0.4t m , where t m It indicates the total duration of the preset ultrasonic treatment, and the total duration of the ultrasonic treatment ranges from 5 to 10 minutes.

[0201] Example 3

[0202] A method for detecting the content of preservatives in food comprises the following steps:

[0203] (1) First, the samples to be tested are classified according to their state: solid samples, liquid samples, and gel samples;

[0204] (2) crushing the solid sample to obtain solid powder, then adding the solid powder sample to pure water, stirring and mixing, and obtaining a first mixed solution;

[0205] For a liquid sample, directly add it into pure water, stir and mix, and obtain a first mixed solution;

[0206] For the gel sample, add it to pure water, heat it to 80°C, keep it warm, and stir it at 5000r / min for 10 minutes to obtain the first mixed solution; the mixing ratio of solid powder to pure water is 2g:25mL;

[0207] The mixing ratio of liquid sample and pure water is 2g:25mL;

[0208] The mixing ratio of the gel sample and pure water is 2g:25mL.

[0209] (3) adding the modified adsorbent to the first mixed solution obtained above, stirring for 10 min, then adding potassium ferrocyanide solution and zinc acetate solution, ultrasonically treating in a water bath at 50° C. for 25 min, then centrifuging at 8000 r / min, filtering, transferring the aqueous phase, and obtaining a first aqueous phase;

[0210] The mixing ratio of the first mixed liquid and the modified adsorbent is 50mL:4g;

[0211] The volume ratio of the first mixed solution, potassium ferrocyanide solution, and zinc acetate solution is 25:1:1;

[0212] The concentration of the potassium ferrocyanide solution is 92 g / L;

[0213] The concentration of the zinc acetate solution is 183 g / L; the preparation method of the modified adsorbent is:

[0214] The pretreated cellulose nanocrystals were added to the sodium hydroxide solution, the temperature was adjusted to 10°C, the mixture was stirred for 15 minutes, and then urea was added, the mixture was stirred and mixed evenly, the temperature was adjusted to 18°C, and the mixture was stirred for 30 minutes to obtain a mixed solution;

[0215] The mixing ratio of pretreated cellulose nanocrystals and sodium hydroxide solution was 11 g: 300 mL;

[0216] The molar ratio of urea to sodium hydroxide is 7:5;

[0217] Adding sodium alginate to deionized water, stirring and mixing evenly to obtain a sodium alginate solution;

[0218] The mass fraction of sodium alginate solution is 5%;

[0219] The sodium alginate solution was added dropwise to the mixed solution and stirred for 10 min to obtain a treated solution;

[0220] The volume ratio of sodium alginate solution and mixed solution is 1:11;

[0221] The montmorillonite is placed in a resistance furnace for calcination for 30 minutes, and then cooled to room temperature to obtain calcined montmorillonite;

[0222] Calcination temperature 456℃;

[0223] Calcined montmorillonite was added to the treatment solution, the temperature was adjusted to 50°C, the mixture was stirred for 40 minutes, calcium chloride solution was added dropwise, stirring was continued for 2 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain a modified adsorbent; the preparation method of pretreated cellulose nanocrystals is as follows:

[0224] First, KH550 was added to the ethanol solution, the temperature was adjusted to 60°C, kept warm, and stirred for 30 minutes to obtain a KH550 solution;

[0225] The cellulose nanocrystals were added to the KH550 solution, the temperature was adjusted to 75°C, the pH was adjusted to 3.5, the mixture was stirred for 4 hours, and then filtered, washed to neutrality, and dried at 70°C for 1 hour to obtain pretreated cellulose nanocrystals; the mass ratio of KH550 to ethanol solution was 1:5;

[0226] Among them, the mass fraction of ethanol solution is 95%;

[0227] The mixing ratio of the cellulose nanocrystals and the KH550 solution is 23 g: 250 mL; the mixing ratio of the calcined montmorillonite and the treatment solution is 32 g: 280 mL;

[0228] The mass fraction of calcium chloride solution is 10%;

[0229] The volume ratio of calcium chloride solution to treatment solution is 1:5.

[0230] (4) adding n-hexane to the first aqueous phase for extraction, then subjecting it to ultrasonic treatment for 6 min, and then subjecting it to centrifugation at a speed of 8000 r / min, standing for 2 hours, removing the organic phase, and obtaining a second aqueous phase;

[0231] Wherein, the volume ratio of the first water phase to n-hexane is 5:1;

[0232] (5) Take 20 mL of the second aqueous phase and filter it through a 0.22 μm filter membrane for liquid chromatography determination;

[0233] Inject the mixed standard series working solutions into the liquid chromatograph respectively, measure the corresponding peak areas, and draw a standard curve with the mass concentration of the mixed standard series working solutions as the abscissa and the peak area as the ordinate;

[0234] The filtered second aqueous phase is injected into a liquid chromatograph to obtain the peak area, and the mass concentration of the preservative in the test solution is obtained according to the standard curve;

[0235] The preservatives include benzoic acid, sorbic acid and saccharin sodium.

[0236] The liquid chromatography parameters are:

[0237] Chromatographic column: C18 column, column length 250 mm, inner diameter 4.6 mm, particle size 5 μm;

[0238] Mobile phase: 5% methanol + 95% ammonium acetate solution;

[0239] Flow rate: 1 mL / min;

[0240] Detection wavelength: 230nm;

[0241] Injection volume: 10 μL.

[0242] The preservative content calculation formula is:

[0243] X = ρV / 1000m;

[0244] X—preservative content in the sample to be tested, in grams per kilogram (g / kg);

[0245] ρ—mass concentration of the sample to be tested in the first mixed solution obtained from the standard curve, in milligrams per liter (mg / L);

[0246] V—volume of the first mixed solution, in milliliters (mL);

[0247] m—mass of the sample to be tested, in grams (g);

[0248] 1000—Conversion factor from mg / kg to g / kg.

[0249] The calculated result of preservative content shall be rounded to 3 significant figures.

[0250] Specifically, after 5-10 minutes of ultrasound, the following steps are performed:

[0251] Volume of n-hexane added for extraction;

[0252] extracting the liquid volume of the first aqueous phase;

[0253] The initial frequency and target frequency of ultrasound are obtained using the added volume of n-hexane and the liquid volume of the first aqueous phase, wherein the initial frequency of ultrasound is obtained by the following formula:

[0254]

[0255] Among them, F c Indicates the initial frequency of ultrasound; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0256] At the same time, the target frequency is obtained by the following formula:

[0257]

[0258] Among them, F m Indicates the target frequency; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0259] The first aqueous phase to which n-hexane is added is ultrasonically treated according to the initial frequency, and the ultrasonic frequency of the ultrasonic treatment is gradually adjusted from the initial frequency to the target frequency, and at the same time, the continuous duration of the ultrasonic treatment at the target frequency is ensured to be not less than 0.4t m , where t m It indicates the total duration of the preset ultrasonic treatment, and the total duration of the ultrasonic treatment ranges from 5 to 10 minutes.

[0260] Example 4

[0261] A method for detecting the content of preservatives in food comprises the following steps:

[0262] (1) First, the samples to be tested are classified according to their state: solid samples, liquid samples, and gel samples;

[0263] (2) crushing the solid sample to obtain solid powder, then adding the solid powder sample to pure water, stirring and mixing, and obtaining a first mixed solution;

[0264] For a liquid sample, directly add it into pure water, stir and mix, and obtain a first mixed solution;

[0265] For the gel sample, add it to pure water, heat it to 80°C, keep it warm, and stir it at 5000r / min for 10 minutes to obtain the first mixed solution; the mixing ratio of solid powder to pure water is 2g:25mL;

[0266] The mixing ratio of liquid sample and pure water is 2g:25mL;

[0267] The mixing ratio of the gel sample and pure water is 2g:25mL.

[0268] (3) adding the modified adsorbent to the first mixed solution obtained above, stirring for 10 min, then adding potassium ferrocyanide solution and zinc acetate solution, ultrasonically treating in a water bath at 50° C. for 28 min, then centrifuging at 8000 r / min, filtering, transferring the aqueous phase, and obtaining a first aqueous phase;

[0269] The mixing ratio of the first mixed liquid and the modified adsorbent is 50 mL: 4.5 g;

[0270] The volume ratio of the first mixed solution, potassium ferrocyanide solution, and zinc acetate solution is 25:1:1;

[0271] The concentration of the potassium ferrocyanide solution is 92 g / L;

[0272] The concentration of the zinc acetate solution is 183 g / L; the preparation method of the modified adsorbent is:

[0273] The pretreated cellulose nanocrystals were added to the sodium hydroxide solution, the temperature was adjusted to 10°C, the mixture was stirred for 15 minutes, and then urea was added, the mixture was stirred and mixed evenly, the temperature was adjusted to 18°C, and the mixture was stirred for 30 minutes to obtain a mixed solution;

[0274] The mixing ratio of pretreated cellulose nanocrystals and sodium hydroxide solution was 11.5 g: 300 mL;

[0275] The molar ratio of urea to sodium hydroxide is 7:5;

[0276] Adding sodium alginate to deionized water, stirring and mixing evenly to obtain a sodium alginate solution;

[0277] The mass fraction of sodium alginate solution is 5%;

[0278] The sodium alginate solution was added dropwise to the mixed solution and stirred for 10 min to obtain a treated solution;

[0279] The volume ratio of sodium alginate solution and mixed solution is 1:11;

[0280] The montmorillonite is placed in a resistance furnace for calcination for 30 minutes, and then cooled to room temperature to obtain calcined montmorillonite;

[0281] Calcination temperature 458℃;

[0282] Calcined montmorillonite was added to the treatment solution, the temperature was adjusted to 50°C, the mixture was stirred for 40 minutes, calcium chloride solution was added dropwise, stirring was continued for 2 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain a modified adsorbent; the preparation method of pretreated cellulose nanocrystals is as follows:

[0283] First, KH550 was added to the ethanol solution, the temperature was adjusted to 60°C, kept warm, and stirred for 30 minutes to obtain a KH550 solution;

[0284] The cellulose nanocrystals were added to the KH550 solution, the temperature was adjusted to 75°C, the pH was adjusted to 3.5, the mixture was stirred for 4 hours, and then filtered, washed to neutrality, and dried at 70°C for 1 hour to obtain pretreated cellulose nanocrystals; the mass ratio of KH550 to ethanol solution was 1:5;

[0285] Among them, the mass fraction of ethanol solution is 95%;

[0286] The mixing ratio of the cellulose nanocrystals and the KH550 solution is 25 g: 250 mL; the mixing ratio of the calcined montmorillonite and the treatment solution is 32 g: 280 mL;

[0287] The mass fraction of calcium chloride solution is 10%;

[0288] The volume ratio of calcium chloride solution to treatment solution is 1:5.

[0289] (4) adding n-hexane to the first aqueous phase for extraction, then subjecting it to ultrasonic treatment for 8 min, and then subjecting it to centrifugation at a speed of 8000 r / min, standing for 2 hours, removing the organic phase, and obtaining a second aqueous phase;

[0290] Wherein, the volume ratio of the first water phase to n-hexane is 5:1;

[0291] (5) Take 20 mL of the second aqueous phase and filter it through a 0.22 μm filter membrane for liquid chromatography determination;

[0292] Inject the mixed standard series working solutions into the liquid chromatograph respectively, measure the corresponding peak areas, and draw a standard curve with the mass concentration of the mixed standard series working solutions as the abscissa and the peak area as the ordinate;

[0293] The filtered second aqueous phase is injected into a liquid chromatograph to obtain the peak area, and the mass concentration of the preservative in the test solution is obtained according to the standard curve;

[0294] The preservatives include benzoic acid, sorbic acid and saccharin sodium.

[0295] The liquid chromatography parameters are:

[0296] Chromatographic column: C18 column, column length 250 mm, inner diameter 4.6 mm, particle size 5 μm;

[0297] Mobile phase: 5% methanol + 95% ammonium acetate solution;

[0298] Flow rate: 1 mL / min;

[0299] Detection wavelength: 230nm;

[0300] Injection volume: 10 μL.

[0301] The preservative content calculation formula is:

[0302] X = ρV / 1000m;

[0303] X—preservative content in the sample to be tested, in grams per kilogram (g / kg);

[0304] ρ—mass concentration of the sample to be tested in the first mixed solution obtained from the standard curve, in milligrams per liter (mg / L);

[0305] V—volume of the first mixed solution, in milliliters (mL);

[0306] m—mass of the sample to be tested, in grams (g);

[0307] 1000—Conversion factor from mg / kg to g / kg.

[0308] The calculated result of preservative content shall be rounded to 3 significant figures.

[0309] Specifically, after 5-10 minutes of ultrasound, the following steps are performed:

[0310] Volume of n-hexane added for extraction;

[0311] extracting the liquid volume of the first aqueous phase;

[0312] The initial frequency and target frequency of ultrasound are obtained using the added volume of n-hexane and the liquid volume of the first aqueous phase, wherein the initial frequency of ultrasound is obtained by the following formula:

[0313]

[0314] Among them, F c Indicates the initial frequency of ultrasound; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0315] At the same time, the target frequency is obtained by the following formula:

[0316]

[0317] Among them, F m Indicates the target frequency; F 0 Indicates the preset ultrasonic initial reference frequency; V zV represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0318] The first aqueous phase to which n-hexane is added is ultrasonically treated according to the initial frequency, and the ultrasonic frequency of the ultrasonic treatment is gradually adjusted from the initial frequency to the target frequency, and at the same time, the continuous duration of the ultrasonic treatment at the target frequency is ensured to be not less than 0.4t m , where t m It indicates the total duration of the preset ultrasonic treatment, and the total duration of the ultrasonic treatment ranges from 5 to 10 minutes.

[0319] Example 5

[0320] A method for detecting the content of preservatives in food comprises the following steps:

[0321] (1) First, the samples to be tested are classified according to their state: solid samples, liquid samples, and gel samples;

[0322] (2) crushing the solid sample to obtain solid powder, then adding the solid powder sample to pure water, stirring and mixing, and obtaining a first mixed solution;

[0323] For a liquid sample, directly add it into pure water, stir and mix, and obtain a first mixed solution;

[0324] For the gel sample, add it to pure water, heat it to 80°C, keep it warm, and stir it at 5000r / min for 10 minutes to obtain the first mixed solution; the mixing ratio of solid powder to pure water is 2g:25mL;

[0325] The mixing ratio of liquid sample and pure water is 2g:25mL;

[0326] The mixing ratio of the gel sample and pure water is 2g:25mL.

[0327] (3) adding the modified adsorbent to the first mixed solution obtained above, stirring for 10 min, then adding potassium ferrocyanide solution and zinc acetate solution, ultrasonically treating in a water bath at 50° C. for 30 min, then centrifuging at 8000 r / min, filtering, transferring the aqueous phase, and obtaining a first aqueous phase;

[0328] The mixing ratio of the first mixed liquid and the modified adsorbent is 50mL:5g;

[0329] The volume ratio of the first mixed solution, potassium ferrocyanide solution, and zinc acetate solution is 25:1:1;

[0330] The concentration of the potassium ferrocyanide solution is 92 g / L;

[0331] The concentration of the zinc acetate solution is 183 g / L; the preparation method of the modified adsorbent is:

[0332] The pretreated cellulose nanocrystals were added to the sodium hydroxide solution, the temperature was adjusted to 10°C, the mixture was stirred for 15 minutes, and then urea was added, the mixture was stirred and mixed evenly, the temperature was adjusted to 18°C, and the mixture was stirred for 30 minutes to obtain a mixed solution;

[0333] The mixing ratio of pretreated cellulose nanocrystals and sodium hydroxide solution was 12 g: 300 mL;

[0334] The molar ratio of urea to sodium hydroxide is 7:5;

[0335] Adding sodium alginate to deionized water, stirring and mixing evenly to obtain a sodium alginate solution;

[0336] The mass fraction of sodium alginate solution is 5%;

[0337] The sodium alginate solution was added dropwise to the mixed solution and stirred for 10 min to obtain a treated solution;

[0338] The volume ratio of sodium alginate solution and mixed solution is 1:12;

[0339] The montmorillonite is placed in a resistance furnace for calcination for 30 minutes, and then cooled to room temperature to obtain calcined montmorillonite;

[0340] Calcination temperature 460℃;

[0341] Calcined montmorillonite was added to the treatment solution, the temperature was adjusted to 50°C, the mixture was stirred for 40 minutes, calcium chloride solution was added dropwise, stirring was continued for 2 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain a modified adsorbent; the preparation method of pretreated cellulose nanocrystals is as follows:

[0342] First, KH550 was added to the ethanol solution, the temperature was adjusted to 60°C, kept warm, and stirred for 30 minutes to obtain a KH550 solution;

[0343] The cellulose nanocrystals were added to the KH550 solution, the temperature was adjusted to 75°C, the pH was adjusted to 3.5, the mixture was stirred for 4 hours, and then filtered, washed to neutrality, and dried at 70°C for 1 hour to obtain pretreated cellulose nanocrystals; the mass ratio of KH550 to ethanol solution was 1:5;

[0344] Among them, the mass fraction of ethanol solution is 95%;

[0345] The mixing ratio of the cellulose nanocrystals and the KH550 solution is 25 g: 250 mL; the mixing ratio of the calcined montmorillonite and the treatment solution is 33 g: 280 mL;

[0346] The mass fraction of calcium chloride solution is 10%;

[0347] The volume ratio of calcium chloride solution to treatment solution is 1:5.

[0348] (4) adding n-hexane to the first aqueous phase for extraction, then subjecting it to ultrasound for 10 min, and then subjecting it to centrifugation at a speed of 8000 r / min, standing it for 2 hours, removing the organic phase, and obtaining a second aqueous phase;

[0349] Wherein, the volume ratio of the first water phase to n-hexane is 5:1;

[0350] (5) Take 20 mL of the second aqueous phase and filter it through a 0.22 μm filter membrane for liquid chromatography determination;

[0351] Inject the mixed standard series working solutions into the liquid chromatograph respectively, measure the corresponding peak areas, and draw a standard curve with the mass concentration of the mixed standard series working solutions as the abscissa and the peak area as the ordinate;

[0352] The filtered second aqueous phase is injected into a liquid chromatograph to obtain the peak area, and the mass concentration of the preservative in the test solution is obtained according to the standard curve;

[0353] The preservatives include benzoic acid, sorbic acid and saccharin sodium.

[0354] The liquid chromatography parameters are:

[0355] Chromatographic column: C18 column, column length 250 mm, inner diameter 4.6 mm, particle size 5 μm;

[0356] Mobile phase: 5% methanol + 95% ammonium acetate solution;

[0357] Flow rate: 1 mL / min;

[0358] Detection wavelength: 230nm;

[0359] Injection volume: 10 μL.

[0360] The preservative content calculation formula is:

[0361] X = ρV / 1000m;

[0362] X—preservative content in the sample to be tested, in grams per kilogram (g / kg);

[0363] ρ—mass concentration of the sample to be tested in the first mixed solution obtained from the standard curve, in milligrams per liter (mg / L);

[0364] V—volume of the first mixed solution, in milliliters (mL);

[0365] m—mass of the sample to be tested, in grams (g);

[0366] 1000—Conversion factor from mg / kg to g / kg.

[0367] The calculated result of preservative content shall be rounded to 3 significant figures.

[0368] Specifically, after 5-10 minutes of ultrasound, the following steps are performed:

[0369] Volume of n-hexane added for extraction;

[0370] extracting the liquid volume of the first aqueous phase;

[0371] The initial frequency and target frequency of ultrasound are obtained using the added volume of n-hexane and the liquid volume of the first aqueous phase, wherein the initial frequency of ultrasound is obtained by the following formula:

[0372]

[0373] Among them, F c Indicates the initial frequency of ultrasound; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0374] At the same time, the target frequency is obtained by the following formula:

[0375]

[0376] Among them, F m Indicates the target frequency; F 0 Indicates the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added;

[0377] The first aqueous phase to which n-hexane is added is ultrasonically treated according to the initial frequency, and the ultrasonic frequency of the ultrasonic treatment is gradually adjusted from the initial frequency to the target frequency, and at the same time, the continuous duration of the ultrasonic treatment at the target frequency is ensured to be not less than 0.4t m , where t m It indicates the total duration of the preset ultrasonic treatment, and the total duration of the ultrasonic treatment ranges from 5 to 10 minutes.

[0378] Comparative Example 1:

[0379] Based on Example 1, no modified adsorbent is added and the rest of the technical solutions remain unchanged.

[0380] Comparative Example 2:

[0381] Based on Example 1, no pretreated cellulose nanocrystals were added in the preparation of the modified adsorbent, and the rest of the technical scheme remained unchanged.

[0382] test:

[0383] The method of Example 1 was tested, and the recovery rate deviation range was statistically analyzed for different concentration levels. The results are shown in Table 1:

[0384] Table 1

[0385] Concentration level range mg / kg Recovery rate range % >100 95-105 1-100 90-110 0.1-1 80-110 <0.1 60-120

[0386] As can be seen from Table 1, the detection range of the method of the present invention is relatively wide and the recovery range is relatively wide.

[0387] Using solid samples as test samples, benzoic acid, sorbic acid and saccharin sodium were tested in the samples respectively. The concentration of each preservative was used as the abscissa and the corresponding peak area was used as the ordinate. Linear regression was performed to compare the linear concentration range:

[0388] Table 2 Benzoic acid

[0389] <![CDATA[Linear concentration range μg·mL -1 > Example 1 0.20-50.33 Example 2 0.20-50.35 Example 3 0.20-50.38 Example 4 0.20-50.30 Example 5 0.20-50.31 Comparative Example 1 0.20-48.63 Comparative Example 2 0.20-49.27

[0390] Table 3 Sorbic acid

[0391] <![CDATA[Linear concentration range μg·mL -1 > Example 1 0.20-49.18 Example 2 0.20-49.46 Example 3 0.20-49.27 Example 4 0.20-49.36 Example 5 0.20-49.22 Comparative Example 1 0.20-46.60 Comparative Example 2 0.20-48.57

[0392] Table 4 Saccharin Sodium

[0393] <![CDATA[Linear concentration range μg·mL -1 > Example 1 0.20-49.03 Example 2 0.20-49.05 Example 3 0.20-49.12 Example 4 0.20-49.15 Example 5 0.20-49.07 Comparative Example 1 0.20-48.02 Comparative Example 2 0.20-48.63

[0394] It can be seen from Tables 2 to 4 that the method of the present invention has a wide linear concentration range for detecting benzoic acid, sorbic acid and saccharin sodium preservatives and a high detection accuracy.

[0395] Benzoic acid, sorbic acid and saccharin sodium were detected by the method of Example 1, and the detection limits were compared:

[0396] Table 5

[0397] Detection limit mg / kg benzoic acid 0.152 Sorbic acid 0.155 Saccharin Sodium 0.154

[0398] It can be seen from Table 5 that the detection limit of the method of the present invention is low and the detection accuracy is high.

[0399] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A method for detecting the content of preservatives in food, characterized in that: The following steps are involved: (1) First, the samples to be tested are classified according to their state: solid samples, liquid samples, and gel samples; (2) crushing the solid sample to obtain solid powder, then adding the solid powder sample to pure water, stirring and mixing, and obtaining a first mixed solution; For a liquid sample, directly add it into pure water, stir and mix, and obtain a first mixed solution; The gel sample is added into pure water, heated to 80°C, kept warm, and stirred at 5000r / min for 10min to obtain a first mixed solution; The first mixed solution was diluted to 50 mL; (3) adding the modified adsorbent to the first mixed solution obtained above, stirring for 10 min, then adding potassium ferrocyanide solution and zinc acetate solution, ultrasonically treating in a water bath at 50° C. for 20-30 min, then centrifuging at 8000 r / min, filtering, transferring the aqueous phase, and obtaining a first aqueous phase; The mixing ratio of the first mixed liquid and the modified adsorbent is 50mL:3-5g; The volume ratio of the first mixed solution, potassium ferrocyanide solution, and zinc acetate solution is 25:1:1; The concentration of the potassium ferrocyanide solution is 92 g / L; The concentration of the zinc acetate solution is 183 g / L; The preparation method of the modified adsorbent is: The pretreated cellulose nanocrystals were added to the sodium hydroxide solution, the temperature was adjusted to 10°C, the mixture was stirred for 15 minutes, and then urea was added, the mixture was stirred and mixed evenly, the temperature was adjusted to 18°C, and the mixture was stirred for 30 minutes to obtain a mixed solution; The mixing ratio of pretreated cellulose nanocrystals and sodium hydroxide solution is 10-12 g: 300 mL; The molar ratio of urea to sodium hydroxide is 7:5; Adding sodium alginate to deionized water, stirring and mixing evenly to obtain a sodium alginate solution; The mass fraction of sodium alginate solution is 5%; The sodium alginate solution was added dropwise to the mixed solution and stirred for 10 min to obtain a treated solution; The volume ratio of sodium alginate solution and mixed solution is 1:10-12; The montmorillonite is placed in a resistance furnace for calcination for 30 minutes, and then cooled to room temperature to obtain calcined montmorillonite; Calcination temperature 450-460℃; The calcined montmorillonite was added to the treatment solution, the temperature was adjusted to 50°C, the mixture was stirred for 40 minutes, the calcium chloride solution was added dropwise, the mixture was stirred for 2 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain a modified adsorbent. The method for preparing the pretreated cellulose nanocrystals is as follows: First, KH550 was added to the ethanol solution, the temperature was adjusted to 60°C, kept warm, and stirred for 30 minutes to obtain a KH550 solution; The cellulose nanocrystals were added to the KH550 solution, the temperature was adjusted to 75°C, the pH was adjusted to 3.5, the mixture was stirred for 4 hours, and then filtered, washed to neutrality, and dried at 70°C for 1 hour to obtain pretreated cellulose nanocrystals. (4) adding n-hexane to the first aqueous phase for extraction, then subjecting it to ultrasonic treatment for 5-10 min, and then subjecting it to centrifugation at a speed of 8000 r / min, standing for 2 hours, removing the organic phase, and obtaining a second aqueous phase; Wherein, the volume ratio of the first water phase to n-hexane is 5:1; (5) Take 20 mL of the second aqueous phase and filter it through a 0.22 μm filter membrane for liquid chromatography determination; Inject the mixed standard series working solutions into the liquid chromatograph respectively, measure the corresponding peak areas, and draw a standard curve with the mass concentration of the mixed standard series working solutions as the abscissa and the peak area as the ordinate; The filtered second aqueous phase is injected into a liquid chromatograph to obtain the peak area, and the mass concentration of the preservative in the test solution is obtained according to the standard curve; The preservatives include benzoic acid, sorbic acid and saccharin sodium.

2. The method for detecting the content of preservatives in food according to claim 1, characterized in that: In step (2), the mixing ratio of solid powder to pure water is 2 g: 25 mL; The mixing ratio of liquid sample and pure water is 2g:25mL; The mixing ratio of the gel sample and pure water is 2g:2mL.

3. The method for detecting the content of preservatives in food according to claim 1, characterized in that: The mass ratio of the KH550 and ethanol solution is 1:5; Among them, the mass fraction of ethanol solution is 95%; The mixing ratio of the cellulose nanocrystals and the KH550 solution is 22-25 g: 250 mL.

4. The method for detecting the content of preservatives in food according to claim 1, characterized in that: The mixing ratio of the calcined montmorillonite and the treatment liquid is 30-33 g: 280 mL; The mass fraction of calcium chloride solution is 10%; The volume ratio of calcium chloride solution to treatment solution is 1:

5.

5. The method for detecting the content of preservatives in food according to claim 1, characterized in that: The liquid chromatograph parameters are: Chromatographic column: C18 column, column length 250 mm, inner diameter 4.6 mm, particle size 5 μm; Mobile phase: 5% methanol + 95% ammonium acetate solution; Flow rate: 1 mL / min; Detection wavelength: 230nm; Injection volume: 10 μL.

6. The method for detecting the content of preservatives in food according to claim 1, characterized in that: The calculation formula of preservative content is: X = ρV / 1000m; X—preservative content in the sample to be tested, in grams per kilogram; ρ—mass concentration of the sample to be tested in the first mixed solution obtained from the standard curve, in milligrams per liter; V—the fixed volume of the first mixed solution, in milliliters; m—mass of the sample to be tested, in grams; 1000—conversion factor from mg / kg to g / kg; The calculated result of the preservative content is retained to 3 significant figures.

7. A method for detecting the content of preservatives in food according to claim 1, characterized in that: The step (4) is then ultrasonicated for 5-10 minutes, comprising: Volume of n-hexane added for extraction; extracting the liquid volume of the first aqueous phase; The initial frequency and target frequency of ultrasound are obtained using the added volume of n-hexane and the liquid volume of the first aqueous phase, wherein the initial frequency of ultrasound is obtained by the following formula: Among them, F c represents the initial frequency of ultrasound; F0 represents the preset initial reference frequency of ultrasound; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added; At the same time, the target frequency is obtained by the following formula: Among them, F m represents the target frequency; F0 represents the preset ultrasonic initial reference frequency; V z V represents the added volume of n-hexane; y represents the liquid volume of the first aqueous phase; F f Indicates the frequency fluctuation amplitude of the ultrasonic vibration equipment during operation; c indicates the concentration percentage of n-hexane; F d It represents the maximum ultrasonic frequency corresponding to the first water to which n-hexane is added; The first aqueous phase to which n-hexane is added is ultrasonically treated according to the initial frequency, and the ultrasonic frequency of the ultrasonic treatment is gradually adjusted from the initial frequency to the target frequency, while ensuring that the continuous duration of the ultrasonic treatment at the target frequency is not less than 0.4t m , where t m It indicates the total duration of the preset ultrasonic treatment, and the total duration of the ultrasonic treatment ranges from 5 to 10 minutes.

Citation Information

Patent Citations

  • Method for testing food additives in foods by virtue of high performance liquid chromatography

    CN107167532A